Analysis of undergraduates' writing in explanation text - Helen, Poh Hang Hua (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aimed to analyze the ability of University Malaysia Sarawak (Unimas) undergraduates in writing texts using the explanation genre. These undergraduates took up the generic course, Academic Reading and Writing (ARW) during semester two of 2007/2008session. These undergraduates taking ARW were taught writing on the genre based approach, where the generic structure and language features peculiar to each genre were emphasized course in year 2007/2008. The undergraduates’ texts used in this study were extracted from their final written examination where one of the questions required them to write a text based on a given diagram by using the explanation genre. A total of 101 sets of these texts (hence known as sample texts) were obtained and analyzed for this study. The focus of this study is on the explanation text type. The analysis was carried out following two checklists based on Derewianka (1990)’s framework, namely the generic structure and language features. The results showed that the undergraduates were familiar with the specific generic structure of the explanation text but there were also a few sample texts with missing and reversed explanation statements. However, language features were the difficult part as most sample texts were found with errors in using appropriate sentence structure in conveying the meaning cohesively and coherently. The implications of the study are discussed and several recommendations with regard to the ARW course are made.